2013
DOI: 10.1177/1744629512472610
|View full text |Cite
|
Sign up to set email alerts
|

The formal support experiences of family carers of people with an intellectual disability who also display challenging behaviour and/or mental health issues

Abstract: This article reports the findings of a literature review of research that has explored the support experiences of family carers of a person with an intellectual disability who displays challenging behaviour and/or has a mental health problem. The purpose of this review is to provide an overview of the reported experiences of family carers from recent research studies, about their own support. Having discussed the search strategy, definitions of challenging behaviour and mental health/illness are presented. Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Previous research has shown that family carers value access to expert staff, continuity in professional relationships, and good two‐way communication that permits effective health information exchange yet regularly report dissatisfaction with services (Kenny & McGilloway, ; McGill, Papachristoforou, & Cooper, ). In particular, family carers of people with intellectual disability report: a lack of partnership working and neglect of family carer knowledge and opinion; a “battle” to be recognised and access support; reactive rather than proactive services in which a crisis situation must be reached before support is received; and lack of clear and understandable information about their relatives condition and care (Douma, Dekker, & Koot, ; Elford, Beail, & Clarke, ; Faust & Scior, ; Griffith & Hastings, ; James, ; McGill, Cooper, & Honeyman, ; Wodehouse & McGill, ). Many of these topics were mentioned in the survey data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that family carers value access to expert staff, continuity in professional relationships, and good two‐way communication that permits effective health information exchange yet regularly report dissatisfaction with services (Kenny & McGilloway, ; McGill, Papachristoforou, & Cooper, ). In particular, family carers of people with intellectual disability report: a lack of partnership working and neglect of family carer knowledge and opinion; a “battle” to be recognised and access support; reactive rather than proactive services in which a crisis situation must be reached before support is received; and lack of clear and understandable information about their relatives condition and care (Douma, Dekker, & Koot, ; Elford, Beail, & Clarke, ; Faust & Scior, ; Griffith & Hastings, ; James, ; McGill, Cooper, & Honeyman, ; Wodehouse & McGill, ). Many of these topics were mentioned in the survey data.…”
Section: Discussionmentioning
confidence: 99%
“…a "battle" to be recognised and access support; reactive rather than proactive services in which a crisis situation must be reached before T A B L E 4 How did you feel about the decision to prescribe medication? support is received; and lack of clear and understandable information about their relatives condition and care (Douma, Dekker, & Koot, 2006;Elford, Beail, & Clarke, 2010;Faust & Scior, 2008;Griffith & Hastings, 2014;James, 2013;McGill, Cooper, & Honeyman, 2010;Wodehouse & McGill, 2009). Many of these topics were mentioned in the survey data.…”
Section: (9)mentioning
confidence: 99%
“…Mothers of children with rare diseases expect health professionals to express their awareness of their limited knowledge, and to be interested in their worries and aspirations (Huyard 2009). They need well-equipped and highly knowledgeable professionals (McGravey and Hart 2008;Allen 2011;James 2013), and action-oriented and abilityrelated information about life expectancy, care and the consequences of rare disease (van den Borne et al 1999;McGravey and Hart 2008;Cassidy and Driscoll 2009;Huyard 2009, Dimitropoulos et al 2013James 2013;Mazaheri et al 2013;Chaij et al 2014). Picci et al (2015) conducted a study that highlights the importance of training and information-providing of physicians for parents of children with rare diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, mental health clinicians developing an understanding of the spirituality of a service user's support system, will likely lead to a more rich understanding of that person and more focused care plans. A literature review on the subject of the support experiences of family carers of people with an intellectual disability, challenging behaviours and mental health problems concluded that there was little research in this area (James, 2013). However, the conclusions of this review did emphasise the importance of care plans being made "in partnership with individual carers" so that family members can be helped to identify the input from professionals they need.…”
Section: Carers and Familiesmentioning
confidence: 92%